2018
DOI: 10.4317/jced.55248
|View full text |Cite
|
Sign up to set email alerts
|

Use of bone scintigraphy in the early diagnosis of bisphosphonate related osteonecrosis of the jaw. Case report and review of the literature

Abstract: The main aim of the present report is to show the potential utility of bone scintigraphy for the diagnosis of jaw osteonecrosis. We report the history of a 62-year-old woman underwent breast cancer surgery in 2010. Moreover, patient received postoperative radiotherapy and chemotherapy. Intravenous bisphosphonates were also added to the treatment strategy to reduce the risk of bone metastasis. However, a hypermetabolic focus on left hemimandible was evidenced with a bone scintigraphy during follow up. After a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The literature reveals that the solid tumors more frequently metastasize to the bone. [19][20][21][22][23] In current study 3 metastatic lesions were found, all of these were in older age group (61-70 years), the literature also show the incidence of metastatic tumors in similar age group. 7,24,25…”
Section: Discussionsupporting
confidence: 62%
“…The literature reveals that the solid tumors more frequently metastasize to the bone. [19][20][21][22][23] In current study 3 metastatic lesions were found, all of these were in older age group (61-70 years), the literature also show the incidence of metastatic tumors in similar age group. 7,24,25…”
Section: Discussionsupporting
confidence: 62%
“…Necrosis of the jaw is associated with BPs, but rarely in patients with AFFs. 21 22 23) Ohbayashi et al 21) reported that the degree of tracer uptake after long-term BP use is notably distinct in the jaw than other bones, including the femur and humerus and they regarded the uptake differences as differences in secondary turnover after primary excessive mineralization by BP and microcracks. Similarly, AFFs were finally considered only after consultation with an orthopedic surgeon due to patient discomfort in the lower extremity or even after sudden complete fractures, although the radiological clue was visible for several months, which was easily neglected ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“… 54 Bone scintigraphy contributes to the early detection of MRONJ in high-risk patients. 55 In animals with MRONJ, the most consistent macroscopic findings are necrosis, denuded bone and formation of fistula and pus. 6 Arce et al assessed patients with MRONJ using six techniques, including films and magnetic resonance imaging.…”
Section: Clinical Staging and Imaging Features Of Mronjmentioning
confidence: 99%